A NNE-trending active graben in the Isparta Angle, SW Turkey: Karamık Graben, its geometry, age and earthquake potential - Çiçek, A.; Koçyičit, A. (TRABAJOS DE GEOLOGÍA, 2009)
the Karamık Graben is an approximately 6-14 km wide, 29 km long, NNE-trending, normal faults-bounded active depression within the Isparta angle included in southwest Turkey extensional domain. It has two graben infills separated by an angular unconformity: (a) a deformed graben infill of Late Early Miocene-Middle Pliocene age, and (b) an undeformed neotectonic infill of Plio-Quaternary age. These two graben infills reveal an episodic history for the Karamık Graben, and a Plio-Quaternary age for the extensional neotectonic period in the Isparta Angle. The northernmost marine boundary of the Karamık Graben was reactivated by the Mw=6.5 Çay earthquake (February, 3rd 2002). However, the rest of the Karamık Graben is a seismic gap threatening settlements in it.